Role of Oxidative Stress in Pathophysiology of Nonalcoholic Fatty Liver Disease. (11th June 2018) - Masarone, Mario; Rosato, Valerio; Dallio, Marcello; Gravina, Antonietta Gerarda; Aglitti, Andrea; Loguercio, Carmelina; Federico, Alessandro; Persico, Marcello
Abstract : Liver steatosis without alcohol consumption, namely, nonalcoholic fatty liver disease (NAFLD), is a common hepatic condition that encompasses a wide spectrum of presentations, ranging from simple accumulation of triglycerides in the hepatocytes without any liver damage to inflammation, necrosis, ballooning, and fibrosis (namely, nonalcoholic steatohepatitis) up to severe liver disease and eventually cirrhosis and/or hepatocellular carcinoma. The pathophysiology of fatty liver and its progression is influenced by multiple factors (environmental and genetics), in a "multiple parallel-hit model, " in which oxidative stress plays a very likely primary role as the starting point of the hepatic and extrahepatic damage. The aim of this review is to give a comprehensive insight on the present researches and findings on the role of oxidative stress mechanisms in the pathogenesis and pathophysiology of NAFLD. With this aim, we evaluated the available data in basic science and clinical studies in this field, reviewing the most recent works published on this topic.